The Influence of Teacher Teaching Creativity on Student Learning Outcomes in Mathematics Subjects - Hardyanti, Venny Siti; Lateef, Hanny; Abbas, Sagir Adamu (jurnal matematika, 2023)
Purpose of the study: to determine the influence of teacher teaching creativity on student learning outcomes in the first semester of fifth grade mathematics in elementary schools. Methodology: The method used is quantitative with a quantitative descriptive research design, data analysis using inductive statistics with research instruments, namely interviews, observation questionnaires and documentation. Main Findings: The results of this research show the teaching creativity of Class V Mathematics Teachers at Sdit Rabbi Radhiyya. does not have a big influence on the learning outcomes of students in the first semester of class V in mathematics, this can be seen from the results of the data analysis obtained, namely 0.174. It is very evident that in the learning process teachers still use the lecture method. Novelty/Originality of this study: It is hoped that this research can provide information for readers and interested parties in knowing the influence of teacher teaching creativity on student learning achievement.